The influence of personal characteristics on entrepreneurial intentions: International comparison - Alice Reissová; Jana Šimsová; Ralph Sonntag; Kristýna Kučerová (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The aim of this study is to establish which factors are the most influential with regard to the development of entrepreneurial intentions (EI) and to establish whether it is the environment (each respondent's country of origin), gender, or personal characteristics the influence of which factor prevails. Research Design & Methods: The created hypotheses were tested using the classification tree method, following a logistic regression. The research population (n=789) comprised students of economic fields from universities in three countries: the Czech Republic, Germany, and the United Kingdom. 'Willingness to run a business' was a dependent variable whereas the countries of respondents' origin, their gender, prior work experience, and personal characteristics (self-reliance, ability to accept risk, creativity, proactivity, and responsibility) were independent variables. Findings: We found that the most significant factor in the willingness to run a business is the ability to accept risk. Other factors, such as the country of origin or respondents' gender, are also statistically significant. Prior work experience did not prove to be a strong predictor. Implications & Recommendations: The results show that the willingness to run a business, which forms an integral part of EI, is to a large extent influenced by relatively stable variables (i.e., personal characteristics, gender, and country of origin). Therefore, it is possible that certain measures aimed at starting and developing a business (e.g., education) will be less effective if the monitored variables (e.g., personal characteristics) are not taken into account. Contribution & Value Added: The added value of this study is the identification and verification of variables influencing business within the international context.
Keywords: M13; 330; entreprenurship; personality; gender; Czech Republic; Germany; United Kingdom